The correlation between serum asprosin and type 2 diabetic patients with obesity in the community - Liang, Dong; Li, Xiaoyu; Xiang, Chenyu; Xu, Minggang; Ren, Yi; Zheng, Fen; Ma, Lijing; Yang, Jing; Wang, Yan; Xu, Linxin (Frontiers in Endocrinology, 2025)
AimsAsprosin is a newly discovered adipokine, it is associated with the insulin resistance, lipid metabolism disorder, diabetes and obesity. However, there have been no reports on the relationship between asprosin and type 2 diabetic patients with obesity. This study aims to investigate the relationship between serum asprosin and type 2 diabetic patients with obesity in the community.Materials and methodsA total of 491 patients with Type 2 Diabetes Mellitus (T2DM) were recruited from Zhuoma Community Care Station and Chengbei West Street Community Care Service Center in Changzhi City of Shanxi Province from November 2019 to July 2021. Patients were divided into the Normal group (n= 145), Overweight group (n=201) and Obesity group (n= 145). The t-test, Mann–Whitney U test, and χ² test were used to compare indicators between the Normal group, Overweight group and Obesity group. Pearson or Spearman correlation analysis was adopted to evaluate the correlation between serum asprosin and other clinical data. Multivariate logistic regression analysis was applied to analyze the influencing factors on obesity. In addition, the diagnostic ability of asprosin to detect type 2 diabetic patients with obesity was tested using receiver operating characteristic (ROC) curve analysis.ResultsCompared with patients with normal weight, the circulating level of asprosin was significantly higher in the obese group than in the normal weight and overweight group (P <0.05). Asprosin was positively correlated with Systolic Blood Pressure(SBP), Body Mass Index (BMI), Waistline, serum uric acid (SUA), aspartate transaminase (AST), creatinine(CRE), and negatively correlated with alanine aminotransferase(ALT). In addition, serum asprosin was significantly correlated with BMI even after adjusting for age, sex, SBP and ALT, SUA, glycosylated hemoglobin (HbA1c), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG) and glomerular filtration rate (eGFR) ((P < 0.05). Compared with the patients in the lowest tertile of serum asprosin (<250.7 pg/mL), patients with asprosin between 250.7–314.0 pg/mL [OR (95% CI) is 1.774 (0.978-3.218), P < 0.05] and asprosin >314 pg/mL [OR (95% CI) is 8.406 (4.788-14.758), P < 0.05] have a higher risk of obesity.ConclusionsSerum asprosin was correlated with obesity in community-based type 2 diabetic patients with obesity. Additionally, the risk of obesity was obviously increased with the raise of asprosin. Therefore, we speculate that serum asprosin could be used as a risk predictor of type 2 diabetic patients with obesity.